Thomas et le Voyageur: Gilles Clément, the landscape, and the planetary garden - Maggiore, Valeria (Aesthetica Preprint, 2024)
The philosophical novel Thomas et le Voyageur: Esquisse du jardin planétaire, written in 1996 by the French landscape architect and agronomist Gilles Clément, is an essential medium for understanding the aesthetic reflections of its author centred on the delicate relationship between environment and landscape, but also (and above all) between landscape “perceived” and “co-created” by human beings. Here, Clément proposes the idea of a garden in motion, qualified as a “laboratory of human-nature relationship”, where the gardener participates in the vital flux of the territory and defends biodiversity without forcing nature but letting it evolve according to the biological cycles. In the garden in motion, the landscape, rather than being “managed” or exploited, is thus observed and accompanied by a kind dialogue. Starting from these premises, Clément promotes, without any internal theoretical contradiction, the idea of the Planetary Garden that, operating an “enlargement of scale”, proposes a responsible approach to the Earth.